ANALISIS KESALAHAN EJAAN DALAM ARTIKEL MAHASISWA UNIVERSITAS ISLAM DARUL `ULUM LAMONGAN - Iib Marzuqi; Anisa Ulfah; Miss Karimah Tayong; Ninik Indah Wahyuni (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe spelling errors in terms of writing letters, writing words, and using punctuation marks in student articles from the Universitas Islam Darul `Ulum Lamongan (Unisda). This research uses a descriptive qualitative method. The data source was obtained from students of the Islamic Unisda with a total of 10 students. The data collection techniques used are documentation, reading, and note-taking techniques. The instrument used to measure spelling errors in student articles from the Islamic Unisda is a data copy sheet. Data analysis techniques carried out in this study were rereading the collected data, analyzing letter writing errors, analyzing word writing errors, analyzing punctuation errors, and concluding the results of the error analysis. Based on this research that has been carried out by researchers, the results found spelling errors are that there are errors in writing letters in student articles from Unisda 221 errors, there are errors in word writing in student articles from Unisda 90 errors, and there are usage errors punctuation in the student's article from the Islamic University Darul Ulum Lamongan 202 errors.